The Role of the Indonesian Ulama Council (MUI) in Religious Authority and Da'wah: A Study of the MUI Fatwa on Pluralism, Liberalism, and Secularism - Andre Parsian; Ali Ridho; Muhammad Aris; Ahmad Irfan; Siti Nuri Nurhaidah (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study aims to analyze the role of the Indonesian Ulema Council (MUI) in a plural society through an examination of MUI Fatwa No. 7/MUNAS VII/MUI/14/2005 concerning pluralism, liberalism, and secularism in religion. The research focuses on investigating how MUI's religious authority functions not only as an institution issuing religious rulings but also as a da'wah communication actor that shapes religious discourse in the public sphere. This study employs a qualitative approach using content analysis and framing analysis to examine the structure, language, and communication strategies embedded in the fatwa text. The findings indicate that MUI possesses strong socio-religious legitimacy in guiding Muslims, as reflected in the normative and authoritative language employed in the fatwa. In addition to serving as a legal guideline, the fatwa functions as a medium of da'wah communication that frames pluralism, liberalism, and secularism as threats to Islamic creed. Through a binary oppositional framing, the fatwa shapes public perceptions regarding the boundaries of religious truth. Within the context of a plural society, the fatwa carries ambivalent implications: it strengthens religious identity while potentially encouraging exclusivism and limiting interfaith dialogue. This study concludes that the MUI fatwa represents a form of authoritative da'wah communication that contributes to the construction of socio-religious norms and realities. Therefore, a more dialogical and inclusive da'wah approach is needed to support social harmony.